Pelatihan Menulis Kreatif dan Menulis Artikel Jurnal Ilmiah untuk Meningkatkan Kemampuan Literasi Guru SMPIT Bakti Ibu Madiun - Kodrat Eko Putro Setiawan; Indra Puji Astuti; Erny Untari; Doni Susanto; Luthfi Ustadziyatul Ummah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
This training on creative writing and writing scientific journal articles aims to improve literacy at the Integrated Islamic Junior High School Bakti Ibu Madiun, especially improving writing skills. The participants of this activity amounted to 20 people. The methods in this training activity are lectures and questions and answers, practice and mentoring. The lecture and question-and-answer method was used to deliver materials related to creative writing and scientific journal articles. The creative writing materials presented included: hierarchy of writing, including ideas consisting of imaginary and factual. Scientific journal article writing materials presented include: the definition of scientific articles, scientific articles for journals, and journal article outlines. The practice and mentoring method was used to follow up on the material that had been delivered in the previous method. This training activity provides benefits, among others: teachers get assistance in creative writing, namely writing interesting experiences when teaching or other activities related to activities at school and writing scientific journal articles, namely writing research related to the learning process at school. The teachers were also given examples and several ways to find references for writing materials used through searches on Google Scholar, mass media or journals in universities.